The development of APIO : Solar Power Plant Based Technology for Automatic Fish Dryer Equipment - Arnita Arnita; Cahayahati Cahayahati; Mirzazoni Mirzazoni (Andalas Journal of Electrical and Electronic Engineering Technology, 2023)
APIO is a fish drying equipment that utilizes sunlight which is converted into electrical energy using a solar power plant. This dryer works automatically using a control system that can control temperature and weight in predetermined settings. APIO designed in the form of a closed box with a heater and fan using a battery as an energy source. APIO uses a load cell and thermocouple as control input using an Arduino microcontroller and regulates the heat temperature in the box between 40-50?C. This tool was tested in the Pasie Nan Tigo Padang, Sumatra Barat. APIO tested using the Arduino uno control at night from 23:00 to 03:15 using fish weighing 5108 grams, data collection was carried out once for 15 minutes for 18 times. The average heater temperature was 32.71?C and the outside temperature was 25?C. The heater voltage was 11.33 V and the heater current was 36.02 A with clear weather conditions. The test results showed a decrease in fish weight to 4208 grams dry. Day time tested from 13:00 to 15:15 using fish weighing 1012 grams, taking data once for 15 minutes for 10 times the average heater temperature is 43.85?C, outside temperature is 30?C and fish weight reaches 208 grams dry.